2018
DOI: 10.1371/journal.pone.0194673
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a prognostic score for hidden cancer in unprovoked venous thromboembolism

Abstract: The usefulness of a diagnostic workup for occult cancer in patients with venous thromboembolism (VTE) is controversial. We used the RIETE (Registro Informatizado Enfermedad Trombo Embólica) database to perform a nested case-control study to validate a prognostic score that identifies patients with unprovoked VTE at increased risk for cancer. We dichotomized patients as having low- (≤2 points) or high (≥3 points) risk for cancer, and tried to validate the score at 12 and 24 months. From January 2014 to October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
2
12
1
1
Order By: Relevance
“…The RIETE score was not able to identify a subgroup of patients with a high risk of occult cancer, contrary to prior validations [ 10 12 ]. When applied only to men, the score was able to identify a subgroup of patients with a high risk of occult cancer, but the performance was poor in the whole group.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The RIETE score was not able to identify a subgroup of patients with a high risk of occult cancer, contrary to prior validations [ 10 12 ]. When applied only to men, the score was able to identify a subgroup of patients with a high risk of occult cancer, but the performance was poor in the whole group.…”
Section: Discussioncontrasting
confidence: 82%
“…The study included patients with unprovoked and provoked VTE, but only 12% of patients with no cancer at VTE presentation were included in the study [ 9 ]. Three validations of the RIETE score have been published [ 10 12 ]. These validations are, however, hampered by several limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When calculating the RIETE score for the population with uVTE, we concluded that 69.5% (N=41) had a score equal or above 3 and, therefore, a risk of occult cancer superior to 10%. According to the score validation trials, this may be the subgroup that benefits the most from ES [18]. In these trials, one-third of the population was at high risk, which leads to the conclusion that our population would have a higher risk.…”
Section: Discussionmentioning
confidence: 93%
“…Several clinical and analytical factors have revealed a predictive value for the identification of patients with uVTE at increased risk of cancer [14][15][16][17]. The Computerized Registry of Patients with Venous Thromboembolism (RIETE) score was validated for this purpose, with the highest risk being present in patients who meet three or more of the following criteria: male gender, age equal or superior to 70 years, chronic lung disease, anemia, thrombocytosis, previous VTE and recent surgery [18]. However, it remains unclear which patients should undergo more extensive screening and whether the earlier detection of cancer improves patients' morbidity, mortality, and quality of life.…”
Section: Introductionmentioning
confidence: 99%